Unfolding the public space: Performing Space or Ephemeral Section of Architecture, PQ 2015. Issue 1 (2nd April 2016) - von Arx, Serge
ABSTRACT: The architecture section of the 2015 Prague Quadrennial (PQ) focused first on scenography as the inherent unifying element of theatre and architecture – not merely the place in which the two meet but the embodiment of their amalgamation. Second, the theatricality of the urban space was central to the PQ 2015 theme of 'Weather, Music, Politics', distinguishing and situating local identities within a common but increasingly expanding context of globalization. The architecture section therefore was called Performing Space or Ephemeral Section of Architecture, raising awareness of and paying tribute to the host city of Prague. Architecture is a time-based art form, experienced with all our senses as we progress through space, and it inheres within it the same performativity of a work's intrinsic evolution in time as scenography. The 2015 Prague Quadrennial's architecture section presented apposite strategies reflecting current international developments of scenography blending into the realm of public space.